Perlindungan Hukum Bagi Pemilik Kartu Elektronik dalam Transaksi E-Commerce - Putu Widhiatmika Coryka; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2021)
An electronic contract is a contract made by the parties through electronic media, each party when negotiating does not need to have a face-to-face meeting but uses electronic media such as email. Currently, electronic contracts have received legitimacy and protection by Law Number 11 of 2008 concerning Electronic Information and Transactions. This study aims to examine the validity of the same as written contracts on credit card ownership agreements and to reveal legal protection for credit card owners in conducting E-commerce transactions. This research was conducted using normative legal research. The sources of legal materials are primary legal materials, which are sourced from legislation and secondary sources of legal materials are taken from relevant literatures with the issues studied. After the research data has been collected, it is then processed and analyzed in a descriptive qualitative way. The results of the study indicate that the legal protection provided by Article 26 of Law Number 8 of 1999 provides protection for consumers by requiring business actors who trade services to fulfill agreed guarantees and or guarantees. An electronic contract is valid evidence if it is presented as evidence at the court table based on article 5 of Law Number 11 of 2008 concerning Electronic Information and Transactions.